A Review on The Enhancement of Biogas Production Through Pre-Treatment of Domestic Wastewater Sludge for Methane Gas Utilization - Almalita Mardiah; Nopa Dwi Maulidiany (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Anaerobic Digestion (AD) is a prevalent and cost-effective method for managing domestic wastewater sludge, often accounting for 20–60% of plant operational costs. This process supports the circular economy by converting organic matter in Waste Activated Sludge (WAS) into renewable biogas. However, WAS is notoriously resistant to degradation due to complex compounds, such as lignocellulose and Extracellular Polymeric Substances (EPS), which severely impede hydrolysis. Therefore, pre-treatment is essential to modify the sludge structure, solubilise organics, accelerate hydrolysis, and enhance methane production. This systematic literature review, conducted according to the PRISMA Checklist 2020, analyses the effectiveness of various pre-treatment methods (mechanical, chemical, physico-chemical, biological, and combined) on domestic sludge. The review found that methane production enhancement varied widely, from 0% to an exceptional 524%, depending on the method and operational parameters. Significantly, combined techniques, such as High-Pressure Homogenisation (HPH) paired with Free Nitrous Acid (FNA), achieved the highest reported increase in methane yield, reaching 524%.